Has the hot hand effect finally been proven? - Birnbaum, P. (Significance, 2015)
A popular belief among sportswriters and broadcasters says that a team that's been successful, should be expected to continue that way. It`s known as the `hot hand` (aka `momentum` or `streakiness`) and the effect is popularly accepted as being real. But almost every study that has looked for such an effect has failed to find one.